Leveraging Artificial Intelligence in Cross-Cultural Mediation: Enhancing Neutrality and Efficiency in Dispute Resolution - Ahmed, Syed Shaharyar; Imam, Mian Johar; Iftikhar, Muhammad Sheharyar (Law and Policy Review, 2025)
International and bilateral relations are often challenged by cultural clashes that hinder communication and compromise the ADR and other legal frameworks. Such culture-related issues may result in suspicion, lack of faith, or rigid attitudes which makes mediation exceedingly difficult. Cross-cultural mediation, defined as dispute resolution that accounts for and integrates relevant cultural differences, has become increasingly important in those cases. While trained mediators are essential in navigating such issues, the additional use of Artificial Intelligence (AI) within Alternative Dispute Resolution (ADR) systems raises new levels of neutrality and efficiency. This research analyzes the impact of AI language models on cultural mediation, focusing on the mitigation of cultural biases, enhanced dispute communication, and advanced automated data dispute analysis. The study evaluates available global approaches and relevant legal documents aiming to demonstrate advantages and restrictions regarding the employment of AI in multi-faceted dispute resolution. The research also addresses an emerging gap in the literature, where the relationship between AI, culture, and ADR have received insufficient academic attention. Ultimately, this paper argues for a balanced approach: one that leverages AI as a support mechanism rather than a substitute for human judgment, while also advocating for modernized legal frameworks to ensure ethical, transparent, and culturally sensitive deployment of AI in mediation and conciliation.